Theta Oscillations and Reactivity of Hippocampal Stratum Oriens Neurons - Valentina F. Kitchigina (The Scientific World Journal)
The supposition was advanced that the neuronal theta rhythmicity is the key mode of signal selection at the hippocampal level. To address this hypothesis, the experimental data on the responses of putative hippocampal interneurons of the stratum oriens CA1-CA3 to stimulation during enhanced theta rhythm and after its blockade are reviewed. Both a strong increase and a decrease of the natural theta rhythm disturbed the reactions of hippocampal neurons; during theta augmentation, the responses were masked or disappeared, and after theta blockade, they lost the ability to habituate. In both cases, two important events were broken: the resetting of the background activity and the phase-locking of theta cycles to stimulus. These data allow one to suppose that only important stimuli are normally capable to evoke these events and these stimuli are selected for recording. When the response to a significant stimulus occurs, the following theta prevents the responses to other stimuli. This probably protects the hippocampal activity from interference from irrelevant signals. Presumably, the absence of the theta deprives the hippocampus of this protection. During enhanced and persistent theta oscillations, the reset disappeared and theta bursts were generated without stimulus locking. In this state, the system is probably closed and the information cannot be recorded. During the theta blockade, the reset was too long and did not habituate. In this case, the system is open for any signals and the hippocampus loses the ability to select signal. This analysis suggests that information selection in the hippocampus may be performed with the participation of nonpyramidal neurons.